Validação e normatização do índice de complexidade da farmacoterapia para idosos atendidos na atenção primária à saúde - Lais Lessa Pantuzza (2017)
Regimen complexity has been associated with negative outcomes, such as hospitalization and non-adherence. Complex regimens are common among the elderly due to the high prevalence of comorbidities and the use of multiple medications by this population. This scenario highlights the need to measure complexity in order to propose strategies to simplify the regimen, increase adherence, treatment effectiveness and safety in medication use. This study objective was to validate and standardize the Brazilian version of the Medication Regimen Complexity Index (MRCI) for the elderly of Primary Health Care; and to evaluate the relationship between regimen complexity and medication adherence by a systematic review. Cross-sectional methodological study carried out with elderly patients attending in Basic Health Units of Belo Horizonte. Convergent validity was tested by correlating MRCI scores with medication number. Divergent validity was tested by correlating MRCI scores with age, gender, cognition, basic and instrumental activities of daily living. Inter and intra-rater reliability were assessed. For standardization it was calculated the percentile posts for total MRCI scores. In the systematic review the databases MEDLINE, LILACS, Cochrane, CINAHL and PsycINFO and the references of the included studies were searched. Clinical, cross-sectional, cohort or case-control studies were included if the relationship between complexity and adherence was quantitatively analyzed in patients of any age and sex under any type of pharmacotherapy. A total of 227 elderly were included, with a mean age of 71.4 years (SD=7,5years) and the majority of females (70.9%). There was correlation between MRCI and medication number (rho=0.890; p=0.000). There was no correlation between MRCI and age (p=0.192), sex (p=0.052), cognition (p=0.267), basic activities (p=0.682) and instrumental activities of daily living (p=0.582). Excellent interrater (ICC=0.981; rho=0.991) and intra-rater (ICC=0.996; rho=0.985) reliability were obtained. It was considered: low complexity: MRCI9.0; mean complexity: 0.9<MRCI16.5 and high complexity: MRCI>16.5. In the systematic review 54 studies were included: 37 cross-sectional and 17 cohorts. More frequently, the studies were carried out with people infected with HIV (10) or patients with chronic conditions: diabetes mellitus (8), epilepsy (3) and arterial hypertension (2). The most frequently method used to measure complexity and adherence were complexity indices (19) and self-report (27), respectively. Regimen complexity was associated with adherence in 35 studies: 28 identified that participants with complex pharmacotherapies were less likely to adhere to their medications; seven studies found a direct correlation between complexity and adherence. The other studies found inconclusive results or no correlation between complexity and adherence. MRCI presented satisfactory psychometric qualities for measuring regimen complexity for the elderly, and standardization may increase MRCI applicability. There was variability regarding the association between complexity and adherence, but the majority of the studies concluded that increasing regimen complexity reduces medication adherence